Nuclear Energy A Volume in the Encyclopedia of Sustainability Science and Technology Series, Second Edition (Encyclopedia of Sustainability Science and Technology Series, 2018)
This book provides an authoritative reference on all aspects of the nuclear energy enterprise for both fission and fusion reactors. Featuring 22 peer-reviewed chapters by recognized authorities in the field, the book offers concise yet comprehensive coverage of fundamentals, current areas of research, and goals for the future. Topics range from fundamental reactor physics calculations, reactor design, nuclear fuel resources, and the nuclear fuel cycle, to radiation detection and protection and the economics of nuclear power. All chapters have been updated from the first edition, with new chapters added on small modular reactors, medical applications - atomic and nuclear, an d applications of radioisotopes. As each chapter is written by an acknowledged expert in the area, the reader can be assured that the text is accurate, up-to-date, and will appeal to a broad audience of undergraduate and graduate students, researchers, and energy industry experts.